THE IMPACT OF PUBLIC HEALTH MESSAGING CAMPAIGNS ON REDUCING EMERGENCY DEPARTMENT VISITS FOR NON-URGENT CONDITIONS - Fahad Owaidh Saeed Almutairi, Eid Sunitan Eid Alotaibi, Saad Hazzaa Gazi Aljsh, Meshal Mohammed Alotaibi, Mushawah Mana R Alanazi, Saad Mohammed Al-Harithi, Arif Mohammed Almutairi, Lafi Ali S Almutairi, Faisal Khalaf Ali Almutairi Naif Hamad Almutairi,,; Muhammad Hamad Almutairi, Abdullah musaad alharbi , Rakan Nahes Alenzi, Faisal Saud Almutairi, Abdalrhman Abdullah Alfawzan, (Chelonian Research Foundation, 2022)
The purpose is to analyze policy measures aimed at decreasing the use of emergency departments (EDs) and to assess their efficacy. A narrative review was conducted by scanning three web databases for scientific literature review publications. The studies' quality was evaluated using the AMSTAR tool, and a narrative synthesis was conducted on the obtained publications. Evaluating interventions is complicated because to the large number of treatments, the many methodologies used to assess outcomes, and the diverse populations involved. While the majority of main studies indicated a decrease in emergency department (ED) use for most therapies, the data presented conflicting outcomes. Despite the presence of multiple publications, the available data on the efficacy of treatments aimed at reducing emergency department (ED) use is still inadequate. Further research is required to investigate the effectiveness of different interventions and their optimal design for certain patient categories. This research should focus on using more uniform patient samples and properly defining both the intervention and control groups. The optimal use of emergency department (ED) services is an intricate and multifaceted issue that needs comprehensive treatments tailored to the unique circumstances of a given nation, along with a feedback mechanism to monitor both intended and unintended outcomes. However, the combination of placing GP posts and emergency departments in the same area, together with the use of telephone triage systems, seems to be the preferable methods for reducing unnecessary trips to the emergency department. Additionally, case-management interventions may be effective in reducing the number of emergency room visits by frequent users. Keywords: Emergency medical services, Health services research, Utilization